Kinetisk kulturanalys: Att följa objekt, rörelser och rytmer - Kamara, Ebrima; Pripp, Oscar (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2010)
Kinetic Cultural Analysis is following the object's movement in time and space and from context to context. To follow "African drums and dance" in this sense is to structure the field. To follow the object's paths is a fieldwork practice as well as an analytical method of interpretation. It could also account for the energy transferred to the analysis and interpretation procedures when change exceeding the boundaries between groups, genres and cultural contexts are as interesting as defining the existence of definable "cultures". In this article, our point is to discuss how this "stalker process" helps qualitatively oriented researchers to navigate large and complex fields. We have been able to look back on the pioneers who introduced African drum and dance in Sweden and investigate the object's motion, and the energy it generates in the cultural process which at the same time enhances the transformation of the context.